The Effect of the Fraud Triangle on Fraud Financial Statements (Case Study on Manufacturing Companies in the Food and Beverage Subsector) - R. Enough Bhaktiar; Awalia Setyorini (Institute of Computer Science (IOCS), 2021)
This study was conducted to analyze the effect of the fraud triangle which consists of financial stability as proxied by ACHANGE, financial targets as proxied by ROA, the nature of the industry as proxied by RECEIVABLE and rationalization proxied by TATA to financial statement fraud as proxied by earnings management. The sample used in this study were 26 food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The type of data used is secondary data in the form of annual reports of companies listed on the IDX during the 2015-2019 period. Hypothesis testing was carried out using multiple linear regression with SPSS 21 software. The results showed that the nature of industry proxied by RECEIVABLE and rationalization proxied by TATA proved to have an effect on financial statement fraud. This study does not prove that financial stability as proxied by ACHANGE and financial targets as proxied by ROA has an effect on fraudulent financial statements.